2020
DOI: 10.1111/odi.13704
|View full text |Cite
|
Sign up to set email alerts
|

Oral potentially malignant disorders: A consensus report from an international seminar on nomenclature and classification, convened by the WHO Collaborating Centre for Oral Cancer

Abstract: Oral potentially malignant disorders (OPMDs) are associated with an increased risk of occurrence of cancers of the lip or oral cavity. This paper presents an updated report on the nomenclature and the classification of OPMDs, based predominantly on their clinical features, following discussions by an expert group at a workshop held by the World Health Organization (WHO) Collaborating Centre for Oral Cancer in the UK. The first workshop held in London in 2005 considered a wide spectrum of disorders under the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
529
1
26

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 617 publications
(685 citation statements)
references
References 139 publications
6
529
1
26
Order By: Relevance
“…Though PVL is a well recognized oral potentially malignant disorder 30 follow‐up studies reporting on malignant transformation have been limited 21 . Retrospective studies reported so far have inherent limitations and multi‐centre prospective studies are needed to explore the natural history of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Though PVL is a well recognized oral potentially malignant disorder 30 follow‐up studies reporting on malignant transformation have been limited 21 . Retrospective studies reported so far have inherent limitations and multi‐centre prospective studies are needed to explore the natural history of this disorder.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review of classification and nomenclature of oral potentially malignant disorders (OPMD) was published by invited experts of the WHO Collaborating Centre for Oral Cancer 1 . OPMDs are a group of mucosal disorders that may precede the diagnosis of oral squamous cell carcinoma (OSCC) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Although many researchers across the globe adopted this term, many discrepancies in describing these disorders are still found leading to inconsistency and confusion. The nomenclature and classification for disorders that precede the development of cancers evolved over the years to align and reflect advances in the understanding of the natural history of these disorders 1 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations